Things that do not fit well, tend to “stand out” – A case report of extrusion of glaucoma drainage device - Devendra Maheshwari; Madhavi R. Pillai; Techi D. Tara; Nimrita Nagdev; Rengappa Ramakrishnan (Kerala Journal of Ophthalmology)
To report a rare case of extrusion of Aurolab aqueous drainage implant (AADI). A 65-year-old male presented with a history of blunt trauma, loss of vision, and irritation in his left eye (oculus sinister [OS]) for 1 year. Two years prior to the presentation, he was diagnosed with pseudophakic secondary glaucoma, for which he underwent implantation of an Aurolab aqueous drainage implant (AADI) in his left eye. Examination revealed phthisis bulbi and a partially extruded body of the AADI plate and tube (OS). The patient underwent surgical explantation of the glaucoma drainage device (GDD) and, subsequently, ocular prosthetic rehabilitation. Extrusion of GDD is a rare occurrence, and timely intervention is necessary to avoid grave consequences.